Associations between the psoas major muscle index and the presence and severity of coronary artery disease. Issue 28 (10th July 2020) - Imaizumi, Tomoki; Shiga, Yuhei; Idemoto, Yoshiaki; Tashiro, Kohei; Ueda, Yoko; Yano, Yuiko-Miyase; Norimatsu, Kenji; Nakamura, Ayumi; Kuwano, Takashi; Iwata, Atsushi; Miura, Shin-Ichiro
Abstract : Abstract: The associations between the presence and severity of coronary artery disease (CAD) and measurements of the psoas major muscle (PMM) as assessed by multidetector row coronary computed tomography angiography (MDCT) are not known. We enrolled 793 patients who were clinically suspected to have CAD or had at least one cardiac risk factor and had undergone MDCT. The number of significantly stenosed coronary vessels (VD) and measurements of the PMM index (PMMI) were determined using MDCT. PMMI in the CAD group was significantly lower than that in the non-CAD group in males, but not females. In addition, the levels of PMMI tended to increase as the number of VD decreased in males. When male patients were divided into 2 groups according to median value of age, that is, relatively younger (53.4 ± 9.2 years) and older (72.6 ± 5.7 years) groups, the presence of CAD was independently associated with PMMI in the younger group by a multiple logistic regression analysis. The cut-off level of PMMI that gave the greatest sensitivity and specificity for the diagnosis of CAD in younger males was 8.3 cm 2 /m 2 (sensitivity 0.441, specificity 0.752). In conclusion, PMMI may be an imaging marker for evaluating the presence and/or severity of CAD in males, and particularly in the non-elderly.